Implementasi Data Warehouse Terhadap Manajemen Aplikasi Gojek Pada Menu Gopay Later - Tegar Adit Tiawan; Nikira Nikira; Juliana Juliana; Sri Indah Ayu Pertama Sari; Nurbaiti Nurbaiti (Jurnal Publikasi Teknik Informatika, 2023)
In this day and age, which is already familiar to Indonesian consumers with digital payment systems, there are so many applications that we can find that regulate digital payment systems, namely one of the delayed payment systems (PayLater), one of which is a well-known application that in Indonesia, GOJEK provides a Gopay Later payment system for customers who use the application to try it. In this era, all payment access is very easy. The purpose of this research is to find out whether the community understands the paylater payment system. This research method uses qualitative research methods using library research, with secondary data collection methods sourced from journals and websites. The results of this study show that almost all online shopping applications have a pay later (paylater) feature, so that people are increasingly aware of developments in the field of fintech technology. So that users of this feature feel that they can make transactions easier because they get lots of promos (cashback) and also free shipping.